Expression of Th17 cell population regulatory cytokines in laryngeal carcinoma – Preliminary study - Kopta, Renata; Mochocki, Marcin; Morawski, Piotr; Brzezińska-Błaszczyk, Ewa; Lewy-Trenda, Iwona; Circle, Student Scientific; Starska, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study was to evaluate the potential role of regulatory and proinflammatory cytokines IL-23 and IL-17 as Th17 lymphocyte activity markers in relation to invasiveness in laryngeal cancer. Material and methods: The immunological analysis was conducted in 50 patients treated for squamous cell laryngeal carcinoma and 30 healthy volunteers as controls. The levels of IL-23 and IL-17 in supernatants of purified peripheral blood mononuclear cell cultures were determined by using the enzyme-linked immunosorbent assay (ELISA). The clinicomorphological criteria included pTNM, stage, G, and the total tumour front grading (TFG) score. Results : Our data demonstrated higher concentrations of IL-23 in patients as compared to controls (p = 0.0001). No statistical difference for IL-17 in these groups was observed. Our study revealed significant dependences in IL-23 expression on pT (p = 0.04), histological differentiation (p = 0.04), and TFG total score (p = 0.02). Advanced tumours (pT3–pT4) with higher grade (G2–G3) and higher invasiveness (> 14 TFG points) were characterised by elevated IL-23 levels in PBMC supernatants. Our data did not indicate a relationship between cytokine levels and three- and five-year survival. However, a tendency towards lower content of IL-23 in PBMC cultures in patients who lived longer than five years after treatment was noted. The relationships between IL-17 level in PBMC cultures and clinicomorphological and prognostic parameters have not been disclosed. Conclusions : The results of this study suggest the importance of regulatory cytokine IL-23 in determining the aggressive potential of laryngeal carcinomas.